Ligand recognition by the major urinary protein - Roy, Julie (2012)
Molecular Dynamics (MD) and Quartz Crystal Microbalance (QCM) techniques can provide unique insights into what drives protein-ligand association. The major urinary protein (MUP) binds small ligands in a deeply buried hydrophobic pocket. Detailed calorimetric studies have shown that ligand binding is driven by enthalpic effects, not entropic effects [1]. Previous studies have shown that this is due to 'dewetting' of the binding site cavity even in the absence of ligands, and have also characterised the complex changes in molecular flexibility that accompany ligand binding-features that may be correlated with NMR data [2]. Recent MD revealed the hydration effects of apo-MUP and also shown where certain regions of MUP become more flexible upon ligand binding. They have also shown a water molecule remains close to the tyrosine in the binding pocket [2]. In our current MD studies and OCM experiments we have used wild type and 2 different mutants of MUP to study the binding effects of the ligand IBM. The first mutant has an OH group removed from the binding site of MUP (i.e. tyrosine to phenylalanine (Y120F)). The second mutant has an extra OH group in the binding site (i.e. alanine to serine (A103S)). For all three systems the hydration and flexibility upon ligand binding has been analysed. The hydration analysis from MD reveal (from radial distribution curves and hydration density maps) there is a small density of water that remains even without the presence of the ligand for the WT MUP whereas a larger density of water remains in the binding cavity of the A103S hydrophilic MUP simulation. The results are based on the average structure generated from the 1 mus simulations. The Y120F MUP simulations reveal that there is no water molecules present in the binding cavity. However, as protein molecules are very dynamic in nature, water molecules are observed to hop in and out of the binding pockets for both mutant MUP (but not WT MUP) simulations over the 1 mus simulations. On the other hand the experimental QCM results reveal that on ligand binding no water loss is observed for Y120F mutant MUP whereas A103S and WT MUP have about 2 water molecules which are lost in the binding cavity. The flexibility results from the MD simulations reveal that WT MUP have some residues which increase in flexibility whilst other residues which decrease in flexibility on ligand binding. However, the Y120F hydrophobic MUP show an overall decrease in flexibility whereas the A103S MUP shows an overall increase in flexibility on ligand binding. In contrast the experimental OCM and AFM results reveal that there is an increase in flexibility on ligand binding to all 3 different types of MUP molecules. The experimental and the simulation data have shown a variation in results but it is to be noted that the results cannot be directly compared as the analytical experiments are a surface based techniques whereas the MD simulations do not involve a surface. However, the contrast observed between computer simulation and experiments has revealed important information on the ligand binding effects on MUP. [1] Bingham, R.J., J.B.C. Findlay, S.Y. Hsieh, A.P. Kalverda, A. Kjeliberg, C. Perazzolo, S.E.V. Phillips, K. Seshadri, C.H. Trinh, W. B. TurnbulI, G. Bodenhausen, and S.W. Homans. 2004. Thermodynamics of binding of 2-methoxy-3-lsopropylpyrazlne and 2- methoxy-3-lsobutylpyrazine to the major urinary protein. J. Am. Chem. Soc. 126:1675-1681. [2] Barratt, E., R.J. Bingham. D.J. Warner, C.A. Laughton, S.E.V. Phillips, and S.W. Homans. 2005. Van der Waals interactions dominate ligand-protein association in a protein binding site occluded from solvent water. J. Am. Chem. Soc. 127:11827-11834.